Beyond moral hazard: the effect of firm-level compensation strategies on economic conflict (2009)
In many countries governments are helpless to prevent appropriation, whatever the degree of protection promised by the law. In this context, we use a simple model where workers can either work peacefully or join a guerrilla movement that expropriates entrepreneurs. We find one low-income, low-wage equilibrium with guerrilla activity and one peaceful, high-income, high-wage equilibrium. We show that the peaceful equilibrium can be reached if entrepreneurs implement standard remedies for the internal principal-agent problem such as efficiency wages.